Estrogen Signaling in ERα-Negative Breast Cancer: ERβ and GPER - Girgert, Rainer; Emons, Günter; Gründker, Carsten (Frontiers in Endocrinology, 2019)
Estrogen receptors are important regulators of the growth of breast tumors. Three different receptors for estrogens have been identified in breast tumors, two nuclear receptors, ERα and ERβ and a G-protein coupled estrogen receptor (GPER) that initiates the non-genomic effects of estrogens in the cytosol. The treatment of breast cancer with anti-estrogens depends on the presence of ERα. About 40% of all breast cancers, however, do not express ERα. One subgroup of these tumors overexpress Her-2, another important group is designated as triple-negative breast cancer, as they neither express ERα, nor progesterone receptors, nor do they overexpress Her-2. This review addresses the signaling of ERβ and GPER in ERα-negative breast tumors. In addition to the well-established EGF-receptor transactivation pathways of GPER more recent findings of GPER-dependent activation of FOXO3a, the Hippo-pathway and HOTAIR-activation are summarized.